(untitled) (Journal of the College of Basic Education, 2024)
The current research aimed to identify auditory perception and the significance of the difference in auditory perception according to the gender variable (males, females) of kindergarten children. To achieve the objectives of the current research, the researcher built an auditory perception scale, and it was applied to the research sample of (358) male and female kindergarten children, according to ( 179 (179) girls were selected using a simple random sampling method for the academic year (2022-2023), and the discriminatory power was extracted and apparent validity was extracted. The reliability of the research tool was verified using the Cronbach method, as the reliability coefficient using the Cronbach alpha method reached (0.93), and the number of items was In its final form for the Auditory Perception Scale (15) items, and after ensuring the validity of the research tool in light of the indicators of validity and reliability and applying the tool to the research sample and then collecting all the data and processing it statistically, the current research reached the following result: The members of the current research sample of kindergarten children enjoy... With voice perception, as for the gender variable (males, females), there is no difference between them, and in light of these results, the researcher presented recommendations, which are to increase attention to children by kindergartens through preparing guidance programs for teachers and educating them to follow the correct methods in their dealings with children, providing them with sensory activities, and encouraging To pay attention to the child and his auditory awareness, support him, and meet his needs. In light of the results and recommendations, the researcher suggests . 1-Conduct a study similar to the current research among samples from other educational levels. 2-Conduct a study linking auditory perception to the variable of curiosity among kindergarten children. 3- Conduct a comparative study of auditory perception among children in public and private kindergartens.